Internalisasi Profil Pelajar Pancasila Dimensi Bernalar Kritis pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 02 Purwokerto - Afif Nurramadhan, Bikri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
With today’s advanced technology, the massive flow of information accelerates the spread of sensitive issues on social media, including those related to Islam. This phenomenon creates an urgency to equip students with critical thinking skills so they can respond to such issues wisely. This is particularly relevant for junior high school students who are beginning to actively access digital information and are vulnerable to provocative content, including religious issues. Critical thinking is also a key competency in developing excellent human resources capable of facing global challenges. For this reason, SMP Negeri 02 Purwokerto as a Junior High School seeks to internalize this ability in its students through the educational process. Therefore, this research aims to explain the Internalization of the Pancasila Student Profile's Critical Thinking Dimension in Islamic Religious Education and Character Education at SMP Negeri 02 Purwokerto as a potential solution to this urgency. This is a field research study employing a descriptive qualitative approach. Data collection methods include interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing and verification. The results of this study show that teachers of Islamic Religious Education and Character Education at SMP Negeri 02 Purwokerto internalize the Critical Thinking Dimension through the following stages: 1) preparing the Islamic Religious Education and Character Education lesson plans; 2) implementing the internalization of the Critical Thinking Dimension in three stages: value transformation, value transaction, and transinternalization; and 3) evaluating the learning process of Islamic Religious Education and Character Education